Peri-implant osteogenesis on alumina-coated titanium implants in rat femur: morphological and elemental analysis of implant surfaces - O. O. Bondarenko; A. H. Bozhko; M. A. Skoryk; N. S. Bondarenko; I. S. Shponka; O. Ye. Loskutov (Zaporozhye State Medical University, 2024)
Peri-implant bone tissue regeneration involves complex processes that are not yet fully understood at the cellular and molecular levels, leaving significant gaps in our knowledge that require further investigation. Aim. The study aimed to compare peri-implant osteogenesis on titanium femoral implants with alumina composite coatings applied by different methods to conventional titanium implants in an animal model. Materials and methods. Implants underwent sandblasting with silicon carbide, plasma torch treatment, and coating with titanium, corundum, sprayed titanium wire, or hydroxyapatite, resulting in seven different surfaces. 105 female Wistar rats received implants in their right femurs and were divided into 7 groups based on implant type and exposure duration (1, 2, or 4 weeks). Implant fragments were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy to quantify chemical elements. Ratios of carbon to nitrogen and calcium to phosphorus were calculated. Data were analyzed using the U-Mann-Whitney test, with р < 0.05 as a significant value. Results. The energy dispersive X-spectrometry results confirmed morphological analysis findings by quantitatively and qualitatively assessing implants surface chemical composition. The key elements were evaluated, relevant for identifying bone tissue components like collagen (C and N) and hydroxyapatite (Ca and P), as well as implant coatings (Ti, Al, Ca, and P). Carbon and phosphorus showed fluctuations over time, with notable differences among groups. Aluminum appeared stable in some groups but varied in others. Calcium levels remained low initially and increased steadily in hydroxyapatite coated implants. Titanium levels were high initially, decreasing slightly over time. Morphological analysis correlated with surface roughness measurements. Notably, fibrin, collagen, and bone tissue presence varied among groups over time, with some groups showing significant mineralized bone tissue accumulation. After four weeks, blood clots persisted in some groups, while others exhibited bone tissue remodeling with the presence of osteoblasts and osteoclasts. Alumina-based coatings showed signs of degradation, with alumina cement scales found among macrophages and fibers. Conclusions. Our study found that stable bone implants outperform alumina-composite coatings in long-term osseointegration due to mechanical stability. Although ceramic composites initially enhance osteoinductive properties, better attachment to titanium substrates is needed.